Predicting the Key Genes Involved in Aortic Valve Calcification Through Integrated Bioinformatics Analysis - Wang, Dinghui; Xiong, Tianhua; Yu, Wenlong; Liu, Bin; Wang, Jing; Xiao, Kaihu; She, Qiang (Frontiers in Genetics, 2021)
Background: Calcific aortic valve disease (CAVD) is regarded to be the most common type of valvular heart diseases and the predominant cause of aortic stenosis in the world. Methods: GSE12644 and GSE51472 were downloaded from GEO database. Then GO and KEGG analysis, STING online tool, cytoscape software were used to identify differentially expressed genes in CAVD and healthy controls, construct a PPI network and then identify key genes. In addition, immune infiltration analysis was used via CIBERSORT to observe the expression of various immune cells in CAVD. Results: A total of 144 differential expression genes including 49 up-regulated genes and 95 down-regulated genes were identified in CAVD compared with healthy group. GO analysis of DEGs were most observably enriched in immune response, signal transduction, inflammatory response, proteolysis, innate immune response and apoptotic process. The KEGG pathway analysis revealed that DEGs were remarkably enriched in chemokine signaling pathway, cytokine-cytokine receptor interaction and PI3K-Akt signaling pathway. CXCL13, CCL19, CCL8, CXCL8, CXCL16, MMP9, CCL18, CXCL5, VCAM1, PPBP were identified as hub genes. It was macrophages that accounted for the maximal proportion among these immune cells. The expression of macrophages M0, B cells memory and Plasma cells were higher in CAVD tissues than in healthy tissues, while the infiltration of B cells naïve, NK cells activated and macrophages M2 were lower. Conclusion: We detected that chemokines CXCL13, CXCL8, CXCL16, CXCL5 and CCL19, CCL8, CCL18 are the most important markers of aortic valve disease. The regulatory macrophages M0, B cells memory, plasma cells, B cells naïve, NK cells activated, macrophages M2 possibly involved in the occurrence and progression of aortic valve stenosis. The identified chemokines and these immune cells may interact with a subtle adjustment relationship in the development of calcification in CAVD.